Experimental and Theoretical Investigation of the Surface Electronic Structure of ZnGa2O4(100) Single‐Crystals. Issue 3 (23rd December 2021) - Reichmann, Felix; Dabrowski, Jaroslaw; Becker, Andreas Paul; Klesse, Wolfgang Matthias; Irmscher, Klaus; Schewski, Robert; Galazka, Zbigniew; Mulazzi, Mattia
Abstract : Herein, a detailed experimental and theoretical investigation on the surface electronic structure of ZnGa2 O4 (100) bulk single‐crystals, with a special emphasis on the surface preparation, is presented. The surface crystallizes in the bulk‐derived structure, even at low annealing temperatures. Thermal treatments in ultra‐high vacuum have detrimental effects, as they cannot remove the carbon contamination and induce substantial zinc losses, further exacerbated by sputtering. A short sputtering duration and annealing in oxygen atmosphere dramatically reduce the zinc and oxygen losses in the crystal surface, leading to a contamination‐free, crystalline surface of nearly stoichiometric composition. The investigation of the valence states along the high symmetry directions of the Brillouin zone compares favorably with ab initio pseudopotential calculations, indicating a good surface quality and overall agreement with theory. An in‐depth analysis of the measured and simulated valence band peak intensities reveals difficulties associated with the precise description of the metal‐oxygen hybridization. This study provides a first fundamental understanding of the electronic structure of ZnGa2 O4, while also indicating that the surface thermal instability is a challenging task that should be taken into account for the fabrication of heterostructures based on ZnGa2 O4 . Abstract : An investigation of ZnGa2 O4 (100) single‐crystals by electron spectroscopy and first‐principles calculations is presented. The surface composition is highly unstable against heating, leading to Zn deficiency. Annealing in oxygen atmosphere drastically improves the surface quality. The resulting electronic structure agrees with calculations, giving the first fundamental insights into the surface electronic structure of the material.